Air water intake device based on heat slow-release system. Issue 3 (June 2021) - Yu, Bingqing; Zhang, Renfei
Abstract: In the arid desert regions of the northwest, fresh water is extremely scarce. But in the desert area's early morning, the day and night temperature are very different, and the air relative humidity will also reach the peak in the day at this time. In this paper, we plan to design an air water intake device in arid area. By using bionics, combining with the traditional water mist water intake method and chimney effect, we design a water intake device to direct the air with high humidity to extract water effectively. The heat release system is designed by using the heat absorption and exothermic characteristics of the phase change energy storage material under the influence of the temperature difference between day and night.